ANSWER
-11ºF > -15ºF
EXPLANATION
You can think of the inequality sign > as an equal sign with one end shrinked. On the shrinked end we have to write the lowest number.
-11ºF is greater than -15ºF, so the expression is
P(1.2) and p+ p(0.2) are equivalent expressions because they both equal to p(1.2).
P=2
Expression 1: P(1.2)=2(1.2)=2.4
Expression 2: P+p(0.2)= 2 + 2(0.2)= 2.4
2.4=2.4
Hope this helps!
Hi there!
First, we "undo" the +49 by subtracting it from both sides of the equation:
x + 49 = 75
x = 75 - 49
x = 26
Hope this helps!
The factored expression which represents the net change in the number of blog subscriptions over 10 months is :
- 3(11 - 7) + 4(-8)
- Hence, the net change is -20
Change : -8, 11, -7, -7, -7, -8, -8, -8, 11, 11
To factor the values in the change variable :
-7 has a frequency of 3
-8 has a frequency of 4
11 has a frequency of 3
Values having the same frequency can be factored together :
Hence, we have ;
3(11 - 7) = 3(11 - 7) = 3(4) = 12 - - - - (1)
-8 having a value of 4 can be factored thus ; 4(-8) = -32 - - (2)
Joining both equations :
3(11-7) + 4(-8)
3(11 - 7) + 4(-8)
3(4) + 4(-8)
12 + (-32)
= - 20
Therefore, the factored expression for the net change in subscription is 3(11-7) + 4(-8)
Learn more :brainly.com/question/18904995
4000(1.05)⁴=$4862.03
6000(1+ .08/2)^35(2)=$93429.71
15450(.86)³=$9827.07